EMPLOYEE ENGAGEMENT DALAM MENINGKATKAN KINERJA EKSPATRIAT - Shofiana, Dyah; Hikmah Perkasa, Didin (LP2M Universitas Bina Bangsa, 2025)
Employee engagement is a crucial element in enhancing individual performance, especially for expatriates working in multinational companies like Perusahaan. This study aims to analyze the impact of employee engagement on expatriate performance in the context of multinational companies. Employee engagement, which includes involvement, commitment, and job satisfaction, has been shown to significantly contribute to individual performance, especially for expatriates facing challenges of cultural adaptation and new work environments. Organizational support, cross-cultural training, and social support networks in the workplace are key factors in enhancing employee engagement. These findings indicate that companies need to develop effective strategies to improve employee engagement to achieve optimal performance from expatriates.